2021
DOI: 10.1371/journal.pone.0248225
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of training—Virtual reality training with augmented multisensory cues improves user experience during training and task performance in the real world

Abstract: Virtual reality (VR) can create safe, cost-effective, and engaging learning environments. It is commonly assumed that improvements in simulation fidelity lead to better learning outcomes. Some aspects of real environments, for example vestibular or haptic cues, are difficult to recreate in VR, but VR offers a wealth of opportunities to provide additional sensory cues in arbitrary modalities that provide task relevant information. The aim of this study was to investigate whether these cues improve user experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 68 publications
(116 reference statements)
0
17
0
1
Order By: Relevance
“…IVR has been argued to be a suitable tool for promoting learning transfer (Cooper et al, 2021;Liu et al, 2017;Narciso et al, 2019), as it offers the possibility for the endless practice of desired skills that can be expensive, dangerous, or even impossible in the realworld setting (Bailenson, 2018). Moreover, VR enables training and learning in different contextual situations with a high level of presence and agency (Makransky & Petersen, 2021).…”
Section: Practical Contributionsmentioning
confidence: 99%
“…IVR has been argued to be a suitable tool for promoting learning transfer (Cooper et al, 2021;Liu et al, 2017;Narciso et al, 2019), as it offers the possibility for the endless practice of desired skills that can be expensive, dangerous, or even impossible in the realworld setting (Bailenson, 2018). Moreover, VR enables training and learning in different contextual situations with a high level of presence and agency (Makransky & Petersen, 2021).…”
Section: Practical Contributionsmentioning
confidence: 99%
“…Nevertheless, prior works reveal that the skills or knowledge acquired in virtual environments can be disconnected from the scenarios in physical world. Therefore, augmented reality can play an auxiliary role in visual cues to remind the acquired skills and knowledge during applicable contexts [24]. Similarly, AR can potentially complement VR to extend the entire cycle of empathic journey -VR aims to elicit users' empathy, while AR reminds users of the experienced empathic scenes in matched contexts, achieving transfers of "empathic learning".…”
Section: Facilitating Empathy In Xr and Metaversementioning
confidence: 99%
“…To this end, it is necessary to link the sole virtual environments with virtual-physical (blended) environments [72,73]. As a prior study revealed that the combination of AR and VR can further engage the users [24], more investigation should be done to achieve the potential of the empathic metaverse.…”
Section: From Virtual Environments To the Metaversementioning
confidence: 99%
“…This could help prime expectations and help subjects keep track of appropriate object interactions. Studies have found that virtual environment performance can impact real world performance [119][120][121][122]. The habits that subjects are forming when interacting with virtual replicas must translate into good practices when using the real-world version of the product.…”
Section: Assessment Of Simulation Claritymentioning
confidence: 99%